Problems of indirect evaluation of dimension change in psychology - Schimunek, F.P. (Psichologija, 1983)
The article analyzes the evaluation problem of dimension change in psychology. The problem of evaluation of specific repeated memorizing is analyzed when summarizing the empirical research. The evaluation methods of change and their features are reviewed; a solution of solving the validity-reliability problem is introduced.